Diagnosing giants : solving the medical mysteries of thirteen patients who changed the world - Mackowiak, Philip A. (Oxford University Press, 2013)
Could Lincoln have lived? After John Wilkes Booth fired a low-velocity .44 caliber bullet into the back of the president's skull, Lincoln did not perish immediately. Attending doctors cleaned and probed the wound, and actually improved his breathing for a time. Today medical trauma teams help similar victims survive-including Gabby Giffords, whose injury was strikingly like Lincoln's. In Diagnosing Giants, Dr. Philip A. Mackowiak examines the historical record in detail, reconstructing Lincoln's last hours moment by moment to calculate the odds. That leads him to more questions: What if he had.